Evaluation of Sperm Impairing Factor from Serratia marcescens as Male Contraceptive in Mouse Model - Chauhan, Aditi (Biomed Res Int, 2019)
The present study was carried out to assess the contraceptive efficacy of sperm agglutinating factor (SAF) isolated from Serratia marcescens, in male Balb/c mice. Mice were administered via an intratesticular route with different concentrations of SAF, viz., 10, 50, 100, 200, or 400 µg, in the right testis only which served as a test while the left side served as control except otherwise stated. Mice were sacrificed on day 3, 7, 14, 21, 30, 45, 60, and 90 after administration, and results in terms of change in body weight, seminal parameters, tissue somatic indices (TSI), hematological parameters, serum level of testosterone, lipid peroxidation, and histology were studied. The body weight and TSI remained unaffected in all the experimental groups. In case of seminal parameters, the right testis treated with 10 μg, 50 μg, 100 μg, 200 μg, or 400 μg of SAF showed azoospermia up to day 7, 14, 21, 45, and 90, respectively. The hematological indices, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were found to be unaltered when the group receiving SAF (test) was compared with the groups receiving phosphate buffer saline (control) in the right testis; however, the treatment had a negative effect on the serum level of testosterone. It also affected the oxidative status of the right testis. Furthermore, histological studies revealed hypospermatogenesis and alterations in the seminiferous tubules which included intraepithelial vacuolation and exfoliation in the right side as compared to the left side. Thus, the results suggest that SAF (400 µg) causes suppression of spermatogenesis, without causing apparent toxic effects.